The book that broke the world eaudiobook - Lawrence, Mark (The Library Trilogy, 2024)
Two people living in a world connected by an immense and mysterious library must fight for those they love in the second book in a new trilogy from the international bestselling author of The Book That Wouldn’t Burn. The Library spans worlds and times. It touches and joins distant places. It is memory and future. And amid its vastness Evar Eventari both found, and lost, Livira Page. Evar has been forced to flee the library, driven before an implacable foe. Livira, trapped in a ghost world, has to recover the book she wrote—one which is the only true threat to the library’s existence—if she's to return to her life. While Evar's journey leads him outside into a world he's never seen, Livira's path will taker her deep inside her own writing, where she must wrestle with her stories in order to reclaim the volume in which they were written.  The secret war that defines the library has chosen its champions and set them on the board. The time has come when they must fight for what they believe, or lose everything.